Centralized Matching with Incomplete Information - Fernandez, Marcelo A.,Rudov, Kirill,Yariv, Leeat (National Bureau of Economic Research, 2021)
We study the impacts of incomplete information on centralized one-to-one matching markets. We focus on the commonly used Deferred Acceptance mechanism (Gale and Shapley, 1962). We show that many complete-information results are fragile to a small infusion of uncertainty about others' preferences
10.3386/w29043
Keywords: Arbeitspapier; Graue Literatur; Matching; Unvollkommene Information